Engineering Metabolism in Nicotiana Species: A Promising Future. Issue 9 (September 2021) - Molina-Hidalgo, Francisco Javier; Vazquez-Vilar, Marta; D'Andrea, Lucio; Demurtas, Olivia C.; Fraser, Paul; Giuliano, Giovanni; Bock, Ralph; Orzáez, Diego; Goossens, Alain
Abstract : Molecular farming intends to use crop plants as biofactories for high value-added compounds following application of a wide range of biotechnological tools. In particular, the conversion of nonfood crops into efficient biofactories is expected to be a strong asset in the development of a sustainable bioeconomy. The 'nonfood' status combined with the high metabolic versatility and the capacity of high-yield cultivation highlight the plant genus Nicotiana as one of the most appropriate 'chassis' for molecular farming. Nicotiana species are a rich source of valuable industrial, active pharmaceutical ingredients and nutritional compounds, synthesized from highly complex biosynthetic networks. Here, we review and discuss approaches currently used to design enriched Nicotiana species for molecular farming using new plant breeding techniques (NPBTs). Highlights: Molecular farming uses crops as biofactories for high value-added compounds by applying a range of biotechnological and engineering tools. The nonfood status, high metabolic versatility, and high biomass production of the genus Nicotiana, specifically the species Nicotiana tabacum and Nicotiana benthamiana, make this plant genus one of the most promising 'chassis' for molecular farming. Tobacco is a rich source of pyridine alkaloids: analyzing the intermediates of the pathway in diverse species and in a temporally and spatially resolved manner will reveal which metabolite pools could serve as precursors for new high value-added compounds. Understanding the chemical diversity combined with recent technological advances in genome sequencing, and the development of NPBTs and synthetic biology tools will open new avenues for metabolic engineering in N. tabacum and N. benthamiana .